Analyzing of Work Performance in Human Capital Sector of Indonesia SMEs: A Systematic Literature Review - Irum Diah Adtuti Sari; Nuzulul Fatimah; Muhammad Gunawa Wibisono (International Journal of Economics, Science, and Education, 2024)
Purpose: This study aims to examine the impact of entrepreneurial orientation on competitive advantage, financial performance, and internationalization among Indonesian firms. By exploring these relationships, the study seeks to highlight how an entrepreneurial mindset drives business success in a dynamic market environment. The investigation focuses on the strategic implications for companies seeking growth and competitiveness in Indonesia’s evolving economic landscape. Design/methodology/approach: The research employs a qualitative with systematic literature review approach, utilizing survey data collected from a sample of Indonesian SMEs and large firms across various sectors. Vosviewer was used to analyze the relationships between work performance on SMEs. Findings: The study finds that entrepreneurial orientation significantly enhances competitive advantage, which in turn positively affects financial performance. Additionally, entrepreneurial orientation directly influences the likelihood of firms pursuing internationalization strategies. Research limitations/implications: The study is limited by its focus on Indonesian firms, which may affect the generalizability of the findings to other markets. Future research could explore similar dynamics in different contexts. Practical implications: The findings suggest that fostering an entrepreneurial culture within firms can enhance competitiveness and financial outcomes, providing valuable insights for managers and policymakers aiming to boost business performance in Indonesia. Originality/value: This study contributes to the literature by specifically examining the interconnected impacts of entrepreneurial orientation in the context of Indonesian firms, offering novel insights into how entrepreneurial practices shape business success in emerging markets. Paper type: Research Paper